2014
DOI: 10.2478/jas-2014-0012
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Bee Larvae to Chalkbrood in Relation to Hygienic Behaviour of Worker Bees in Colonies of Chosen Races of Honeybee (Apis Mellifera )

Abstract: A b s t r a c t the susceptibility of bee larvae to Ascosphaera apis infestation and the hygienic behaviour of worker bees in relation to A. apis infected and freeze-killed brood were evaluated in three races of bees: Apis mellifera carnica, Apis mellifera caucasica, and Apis mellifera mellifera. experimental bee colonies were evaluated in field conditions during the three beekeeping seasons. the lowest percentage of infected larvae was observed in car gR1 and mel A colonies (8.5% and 15%, respectively) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…FKB and FKB* are two ways to measure the same trait, i.e., the dead removal ability of a bee colony. We did not investigate in this study the correlation of HB with the biological trait of interest as previous reports showed that HB can be used as a proxy to select colonies for resistance to main brood pathogens (Spivak and Reuter, 2001;Panasiuk et al 2008;Panasiuk et al 2014). FKB* requires less time and liquid nitrogen and has a smaller measurement error, resulting in a slightly higher repeatability.…”
Section: Resultsmentioning
confidence: 99%
“…FKB and FKB* are two ways to measure the same trait, i.e., the dead removal ability of a bee colony. We did not investigate in this study the correlation of HB with the biological trait of interest as previous reports showed that HB can be used as a proxy to select colonies for resistance to main brood pathogens (Spivak and Reuter, 2001;Panasiuk et al 2008;Panasiuk et al 2014). FKB* requires less time and liquid nitrogen and has a smaller measurement error, resulting in a slightly higher repeatability.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, at day 9, there was a high proportion of strong grooming. Panasiuk et al demonstrated that hygienic behaviors involve bees across various age ranges but are more commonly observed between 6 to 10 and 16 to 21 of age [ 21 ]. Pettis and Pankiw studied the role of grooming behavior in bees based on the bees’ age, revealing that approximately 90% of grooming behavior occurred in bees between 5 and 15 days old [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to negatively affecting the growth and production of colonies, pathogens and diseases cause significant economic losses for beekeepers (Panasiuk et al, 2014), and some management practices can be used to mitigate colony losses. Berry & Delaplane ( 2001) suggested replacing old honeycombs or those with symptoms of A. apis as an initial management technique to eliminate spores from the hive.…”
Section: Management Strategies To Reduce Risk Of Colony Lossesmentioning
confidence: 99%